Effect of variations in front wheels driving lead on performance of a farm tractor with mechanical front-wheel-drive. (June 2018) - Janulevičius, Algirdas; Damanauskas, Vidas; Pupinis, Gediminas
Highlights: When adjusting a tractor slip, there may be changes in driving lead of front wheels. Combination pressures in the tires, generating a well-targeted lead of front wheels. Lead of front wheels plays a significant role in controlling the fuel consumption. Combining pressures in the tires a few change slip but can reduce fuel consumption. Abstract: Most previous researches indicate that about 20–55% of available tractor power is lost in the process of interaction between tires and soil surface. Vertical wheel loads and tire performance are parameters that play a significant role in controlling slip and fuel consumption of a tractor. Tractor's slip is adjusted by attaching additional weights and/or reducing tire pressures, and this may have an impact on driving lead of front wheels. Mechanical Front-Wheel-Drive (MFWD) tractors work efficiently when driving lead of front wheels is 3–4% in soft soil and 1–2% in hard soil. This research was aimed to experimentally determine such tire pressures that allow adjusting tractor's slip without deviating from set value of driving lead of front wheels. The research was also aimed to determine the effect of driving lead of front wheels on MFWD tractor's slip and fuel consumption. Experimental results showed that front/rear tire pressure combinations that generate a well-targeted driving lead of front wheels have no effect on slip on hard soil; however, it significantly affect fuel consumption. Results show that when air pressures in front/rear tires varied within 80–220 kPa, driving lead of front wheels varied in the range from +7.25% to −0.5%.